Minimization of Boolean expressions using matrix algebra - Holger Schwender (Universität Dortmund, Sonderforschungsbereich 475 - Komplexitätsreduktion in Multivariaten Datenstrukturen, 2007)
The more variables a logic expression contain, the more complicated is the interpretation of this expression. Since in a statistical sense prime implicants can be interpreted as interactions of binary variables, it is thus advantageous to convert such a logic expression into a disjunctive normal form consisting of prime implicants. In this paper, we present two algorithms based on matrix algebra for the identification of all prime implicants comprised in a logic expression and for the minimization of this set of prime implicants.
Keywords: 519; Logik; Matrizenrechnung; Mathematische Optimierung; Theorie